Integrated Strategic Communication (ISC) in Romanian Organizations: Array - Tureac, Cornelia Elena; Popa, Doinita; Panaitescu, Manuela Carmen (Didactica Danubiensis, 2022)
In the last 10-15 years, we have witnessed remarkable technological changes and particularly spectacular innovations, which have led to a complete change in the way business develops, in the way communication changes or in the way we choose to live our lives. All these changes have forced organizations to develop and improve their customer relationships and try to find solutions to convey consistent messages in their interactions with all interested parties - the state and local authorities, their own employees, suppliers, financial institutions - using a wide range of integrated communication tools.